1999
DOI: 10.1111/j.1439-0450.1999.tb01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transmission of Theileria annulata to Cattle by the Tick Hyalomma lusitanicum

Abstract: The role of the ixodid tick Hyalomma lusitanrcum Koch 1844 as a vector of Mediterranean or tropical theileriosis (caused by the protozoan parasite Theileria annul& Dschunkowsky et Luhs 1904) in southern Spain was studied. Hyalomma lusitanicum was the most common uck, and the only species of the genus Hyalomma L., found on 7: onndata-infected cattle from the theileriosis enzootic area studied (province of Cadiz, southern Spain). Likewise, we found that all sera of the cattle previously considered as suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 2 publications
0
17
0
1
Order By: Relevance
“…Hyalomma, Rhipicephalus and Dermacentor species are vectors of piroplasmids (reviewed by Homer et al 2000), and Viseras et al (1999) suggested Hy. lusitanicum as a vector for T. annulata in southern Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Hyalomma, Rhipicephalus and Dermacentor species are vectors of piroplasmids (reviewed by Homer et al 2000), and Viseras et al (1999) suggested Hy. lusitanicum as a vector for T. annulata in southern Spain.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a transmission cycle with such new vectors could happen if tropical theileriosis is already endemic in the region or when carrier animals are introduced in the cattle population due to animal movement but in the absence of previously established transmission cycles. This scenario has been observed for H. dromedarii in southern Mauritania (Jacquiet et al, 1994) and H. lusitanicum in Spain (Viseras et al, 1999) (3) The spread, under the influence of several driving forces (see below), of known natural vector ticks and the pathogen via animal movements to non-endemic zones. The discovery of tropical theileriosis in Mauritania is one of the best example illustrating this scenario.…”
Section: Distribution Of T Annulata Infectionsmentioning
confidence: 90%
“…Major natural vector in Mauritania (Jacquiet et al, 1990(Jacquiet et al, , 1994 Major natural vector in Spain (Viseras et al, 1999). Potential secondary vector in parts of Morocco and Algeria Life cycle and hosts (i) Tick species with a strong biological adaptation to arid conditions, , Walker et al, 2003 Under cold Mediterranean climates, the adults are active during the summer with a peak in July and the larvae and nymphs are active during the autumn.…”
Section: H Lusitanicummentioning
confidence: 99%
“…It is almost certain that H. lusitanicum is a vector of Theileria annulata (Dschunkowsky et Luhs, 1904) Wenyon, 1926(Habela et al 1999, Viseras et al 1999 Hoogstraal, 1956 We consider the most useful descriptions and illustrations of the adults to be those in Tonelli Rondelli (1932), Hoogstraal (1956) and Hoogstraal and Kaiser (1958a, b). The larva and nymph have never been described.…”
Section: Disease Relationshipsmentioning
confidence: 99%